Bankruptcy Risk Classification of Plastic and Packaging Firms on the IDX: Klasifikasi Risiko Kebangkrutan Perusahaan Plastik dan Kemasan di Bursa Efek Indonesia (IDX) - Fani Ismidiyah; Heri Widodo (Indonesian Journal of Law and Economics Review, 2025)
General Background Financial distress remains a critical issue for manufacturing firms, particularly in sectors facing regulatory and economic pressure. Specific Background Plastic and packaging subsector companies listed on the Indonesia Stock Exchange experienced financial dynamics during 2020–2022 amid economic disruption and recovery. Knowledge Gap Limited empirical studies focus on bankruptcy risk classification within this subsector using updated post-pandemic financial data. Aims This study aims to analyze the potential bankruptcy condition of plastic and packaging subsector companies listed on the IDX during 2020–2022 using the Altman Z-Score model. Results The findings show that several companies consistently remained in the safe zone, while others persistently fell into the bankruptcy zone, and some demonstrated gradual financial recovery across the observation period. Novelty This research provides updated evidence on bankruptcy risk patterns in the plastic and packaging subsector during a critical economic period using the Altman Z-Score approach. Implications The results offer practical insights for corporate management, investors, and stakeholders to monitor financial health and apply early warning mechanisms for bankruptcy prevention. Keywords: Altman Z-Score, Bankruptcy Risk, Financial Ratios, Plastic and Packaging Subsector, Indonesia Stock Exchange Key Findings Highlights: Financial conditions across firms varied significantly during the 2020–2022 period Several companies showed persistent financial distress across three consecutive years Early detection using ratio-based models supports strategic financial monitoring